1993
DOI: 10.1152/jn.1993.70.5.2056
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization-activated currents in neurons of the rat basolateral amygdala

Abstract: 1. A single microelectrode was used to obtain current-clamp or voltage-clamp recordings from two neuronal cell types (pyramidal and late-firing neurons) in the basolateral nucleus of the amygdala (BLA) in slices of the rat ventral forebrain. Conductances activated by hyperpolarizing voltage steps from a holding potential of -70 mV were identified and their sensitivity to muscarinic modulation was determined using bath superfusion of carbachol. 2. Unclamped pyramidal neurons exhibited anomalous rectification, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 0 publications
4
37
1
Order By: Relevance
“…In response to depolarizing current injection of increasing amplitude, neurons initially fired either a single action potential or a doublet/triplet burst, after which a slower, more rhythmic firing pattern was observed (Figure1a, top). These neurons also showed a depolarizing sag in the voltage excursion in response to hyperpolarizing current pulses (Figure1a, bottom) (Womble and Moises, 1993). Initially, using current-clamp mode, we showed that bath pretreatment with L-P NPY (200 or 400 nM) induced a significant increase of evoked inhibitory postsynaptic potentials (eIPSPs) (RM-ANOVA 200 nM L-P NPY: F (2,18) ÂŒ 5.13, P ÂŒ 0.017; 400 nM L-P NPY: F (2,18) ÂŒ 5.8, P ÂŒ 0.011; Figure 1b), which differed significantly from baseline during both 200 and 400 nM drug application (P ÂŒ 0.01 and 0.01, respectively, Dunnett's) and remained significantly increased from baseline during wash for 400 nM dose (P ÂŒ 0.02, Dunnett's; Figure 1b).…”
Section: Resultsmentioning
confidence: 95%
“…In response to depolarizing current injection of increasing amplitude, neurons initially fired either a single action potential or a doublet/triplet burst, after which a slower, more rhythmic firing pattern was observed (Figure1a, top). These neurons also showed a depolarizing sag in the voltage excursion in response to hyperpolarizing current pulses (Figure1a, bottom) (Womble and Moises, 1993). Initially, using current-clamp mode, we showed that bath pretreatment with L-P NPY (200 or 400 nM) induced a significant increase of evoked inhibitory postsynaptic potentials (eIPSPs) (RM-ANOVA 200 nM L-P NPY: F (2,18) ÂŒ 5.13, P ÂŒ 0.017; 400 nM L-P NPY: F (2,18) ÂŒ 5.8, P ÂŒ 0.011; Figure 1b), which differed significantly from baseline during both 200 and 400 nM drug application (P ÂŒ 0.01 and 0.01, respectively, Dunnett's) and remained significantly increased from baseline during wash for 400 nM dose (P ÂŒ 0.02, Dunnett's; Figure 1b).…”
Section: Resultsmentioning
confidence: 95%
“…However, in other neurones Ih can contribute substantially to the resting and active properties of neurones, e.g. thalamic relay neurones (McCormick & Pape, 1990), hippocampal neurones (Maccaferri et al 1993;Gasparini & DiFrancesco, 1997), neurones of the basolateral amygdala (Womble & Moises, 1993) and ventrobasal thalamic neurones (Williams et al 1997). The reasons why Ih is active at rest in some neurone types and not in others is unclear at present.…”
Section: Discussionmentioning
confidence: 95%
“…Pharmacologically, Ih can be discriminated from other hyperpolarization-activated currents such as inward rectifier potassium currents because it is not blocked by intracellular Cs€ or extracellular Ba„ (Womble & Moises, 1993). The use of the bradycardiac agent ZD7288, developed as an inhibitor of If (the cardiac hyperpolarization-activated cation current), provides further pharmacological evidence that Ih is the neuronal equivalent of If.…”
Section: Discussionmentioning
confidence: 99%
“…Speculations on the nature of I INS reach from models where this current represents a leak conductance or an experimental artifact to models in which I INS is caused by a second pore that is found within the same HCN channel that produces I SS or a second channel population associated with HCN channels (236,237,312). Depending on the cell type, the activation of I SS can be empirically described by either a single (120,136,200,261,264,355,393,425) or double exponential function (17,104,131,175,248,402). As mentioned above, kinetics of I SS are quite variable (111,118).…”
Section: A Channel Gating By Membrane Hyperpolarizationmentioning
confidence: 99%